Comparison of Moderate- to High-Astigmatism Corrections Using WaveFront–Guided Laser In Situ Keratomileusis and Small-Incision Lenticule Extraction. Issue 4 (April 2016) - Zhang, Jiamei; Wang, Yan; Chen, Xiaoqin
Abstract : Purpose: To evaluate and compare refractive outcomes of moderate- and high-astigmatism correction after wavefront–guided laser in situ keratomileusis (LASIK) and small-incision lenticule extraction (SMILE). Methods: This comparative study enrolled a total of 64 eyes that had undergone SMILE (42 eyes) and wavefront–guided LASIK (22 eyes). Preoperative cylindrical diopters were ⩽−2.25 D in moderate- and >−2.25 D in high-astigmatism subgroups. The refractive results were analyzed based on the Alpins vector method that included target-induced astigmatism, surgically induced astigmatism, difference vector, correction index, index of success, magnitude of error, angle of error, and flattening index. All subjects completed the 3-month follow-up. Results: No significant differences were found in the target-induced astigmatism, surgically induced astigmatism, and difference vector between SMILE and wavefront–guided LASIK. However, the average angle of error value was −1.00 ± 3.16 after wavefront–guided LASIK and 1.22 ± 3.85 after SMILE with statistical significance ( P < 0.05). The absolute angle of error value was statistically correlated with difference vector and index of success after both procedures. In the moderate-astigmatism group, correction index was 1.04 ± 0.15 after wavefront–guided LASIK and 0.88 ± 0.15 after SMILE ( P < 0.05). However, in the high-astigmatism group, correction index was 0.87 ± 0.13 after wavefront–guided LASIK and 0.88 ± 0.12 after SMILE ( P = 0.889). Conclusions: Both procedures showed preferable outcomes in the correction of moderate and high astigmatism. However, high astigmatism was undercorrected after both procedures. Axial error of astigmatic correction may be one of the potential factors for the undercorrection.